The effect of mental fatigue on boxing performance - Salam, H.; Faraj, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Mental fatigue has been shown to reduce physical performance in endurance sports (Marcora, 2009a). Recent studies have demonstrated a negative effect of cognitive tasks involving response inhibition on perception of effort during self-paced endurance tasks (Marcora et al., 2009b; Salam et al., 2017). By comparison, there is a paucity of research investigating the effects of mental fatigue on high intensity intermittent sports, such as boxing, which, even though shorter in duration, has been shown to effect psychological states in boxers (Slimani et al., 2002). Therefore, the aim of this study was to investigate the effect of mental fatigue on boxing physical performance. METHODS: Sixteen elite boxers completed 3 laboratory visits, the first was to familiarize participants with the experimental protocol. During the experimental visits, each boxer completed three rounds of boxing performance. In the first round, boxers performed 1000 jab and cross punches, in second round 1000 left and right hooks, and in final round 1000 left and right uppercuts punches. There was a 60 second rest period between each round. Prior to these exercise bouts boxers completed either mentally fatiguing task (MF) or a control condition (CC). Within the MF condition, undertook a 30-min incongruent Stroop Task designed to induce perceptions of MF. Within the CC condition participants spent 30-min reading a magazine, and the Brunel mood scale (BRUMS) questionnaire were assessed before and immediately after each condition. During rest periods between rounds, blood lactate, heart rate, and RPE were taken. Data were analysed by two-way (2 condition x 3 time points) repeated-measures ANOVAs. RESULTS: The MF task induced negative change in boxing performance duration, so the comparison of 1000 punch time expenditure were: the first round (CC 392 ± 8 sec vs. MF 446 ± 3 sec), second round (CC 370 ± 14 vs. MF442 sec ± 6 sec) and third round (CC 338 ± 12 sec vs. MF385 ± 7 sec) (Boxers spent longer time in MF condition compare to CC (P0.05). However, the BL accumulation was significantly lower in MF condition (P < 0.05). CONCLUSION: The results of this study demonstrate that MF has a direct negative effect of boxing performance duration, RPE, and perception of mental fatigue.